Mentoring, Institutional Barriers, Structures of Justice: A Dialogue Across Positions of Privilege and Power - Dell'Antonio, Andrew; Ovalle, Matthew (Current Musicology, 2021)
This colloquy, by graduate-student-led collective Project Spectrum, attempts to map out existing discussions around inclusion and equity in music academia, with a specific focus on identifying and analyzing the structures in academia that work against minoritized and historically excluded scholars. Matthew Ovalle and Andrew Dell’Antonio contribute a joint-paper outlining the alternative pathways that give people the chance to make their own way through the music academia pipeline. Using personal anecdotes from their positions as teachers, mentors, and the mentored, they offer a representation of academia as one of care, empathy, and optimism.